(untitled) (Research, Society and Development, 2022)
Introduction: Adverse Food Reactions (AAR) are any abnormal reaction to the ingestion of food or food additives, Introduction: Lactose intolerance is characterized by the absence of an enzyme in the body, called lactase. The probiotic Kefir was presented as a strategy for the prevention and/or treatment of gastrointestinal disorders and microbiota modulation, due to its functional properties and because it contains beneficial microorganisms such as lactic acid bacteria (LAB) of the lactobacillus genera. and bifidobacterium that act as a restorer causing the balance of the intestinal microbiota. Objective: To identify the beneficial and nutritional effects related to milk kefir, to analyze the influence of the probiotic on lactose intolerance and to describe the therapeutic potential of milk kefir in intestinal modulation. Methodology: The study was carried out through a literature review based on scientific articles, gathering and evaluating several studies related to the topic. Results: It was evaluated that the regular consumption of the probiotic kefir has great importance on the balance and modulation of the intestinal microbiota, in the symptoms of lactose intolerance, immune system, in addition to playing an antifungal, antibacterial and antioxidant role. Discussion: The importance of this probiotic still little known and consumed by the population was understood, since milk kefir has numerous health benefits, prevention and treatment of some pathologies, especially gastrointestinal diseases. Conclusion: In general, it was concluded that milk kefir is an excellent alternative to be included in the diet of lactose intolerant people, since it has several advantages and health benefits, low cost and great viability.